The intronic G13964C variant in p53 is not a high-risk mutation in familial breast cancer in Australia - Marsh, Anna (BioMed Central, 2001)
BACKGROUND: Mutations in BRCA1 and BRCA2 account for approximately 50% of breast cancer families with more than four affected cases, whereas exonic mutations in p53, PTEN, CHK2 and ATM may account for a very small proportion. It was recently reported that an intronic variant of p53 - G13964C - occurred in three out of 42 (7.1%) 'hereditary' breast cancer patients, but not in any of 171 'sporadic' breast cancer control individuals (P = 0.0003). If this relatively frequent occurrence of G13964C in familial breast cancer and absence in control individuals were confirmed, then this would suggest that the G13964C variant plays a role in breast cancer susceptibility. METHOD: We genotyped 71 familial breast cancer patients and 143 control individuals for the G13964C variant using polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) analysis. RESULTS: Three (4.2%; 95% confidence interval [CI] 0–8.9%) G13964C heterozygotes were identified. The variant was also identified in 5 out of 143 (3.5%; 95% CI 0.6–6.4%) control individuals without breast cancer or a family history of breast cancer, however, which is no different to the proportion found in familial cases (P = 0.9). CONCLUSION: The present study would have had 80% power to detect an odds ratio of 4.4, and we therefore conclude that the G13946C polymorphism is not a 'high-risk' mutation for familial breast cancer.